My hero academia. Vol. 2, Rage, you damned nerd - Horikoshi, Kohei, 1986-; Cook, Caleb D. (Shonen Jump manga., 2015)
Getting into the Hero Academy because he was given the powers of All Might is one thing, but learning to control those powers is quite another for Midoriya, who for most of his life was "quirkless," without any superhero abilities at all. Now he must compete against his fellow classmates just to keep from expulsion.